Edukasi Pentingnya Mangrove Bagi Lingkungan Pesisir di Desa Lembar Selatan, Kecamatan Lembar, Kabupaten Lombok Barat - Affandi, Rangga Idris; Diniariwisan, Damai; Rahmadani, Thoy Batun Citra; Sumsanto, Muhammad; Diamahesa, Wastu Ayu (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Coastal areas are transition between land and marine ecosystems. The coast is an area rich in natural potential which has long been utilized by humans. Changes that occur in coastal and marine areas are generally influenced by human activities in the surrounding areas, resulting in a decline in environmental quality, one of which is the mangrove ecosystem. Mangrove are spread throughout almost all coastal areas in Indonesia. The mangroves in South Lembar Village are directly adjacent to settlements, coastal tourist areas and aquaculture. Therefore, it is necessary to transfer knowledge so that the community of South Lembar Village, especially those on the coast, understand the importance of mangroves for the environment so that they can protect the mangrove ecosystem. The implementation of this community service activity is carried out using the counseling method. This service activity began with a presentation on the importance of the mangrove ecosystem and a question and answer/discussion. The result of this community service was that outreach was carried out with material presented regarding the importance of the mangrove ecosystem, which was attended by the South Lembar Ecotourism Group and the Cemare Eco Green Mangrove Society, the South Lembar Village community, and lecturers from the Aquaculture Study Program. The conclusion of this community service is that information, knowledge and science have been conveyed to the community in Cemare Hamlet, South Lembar Village about the importance of mangrove ecosystems for marine coastal areas. Further community service activities are needed in the form of mangrove planting.